YOU (YES, YOU) ARE SMART ENOUGH TO . - BOYLE, ANDY (Quill)
In this article the author explains the importance of learning basic coding skills by journalists as daily work becomes easy and they learning to solve new problems and learn new tools. He explains the obvious benefits to learning how to code. He provides information on Internet tools which can help to create and edit web pages, and motivates to learn coding on your own.